AB0917 Safetey and efficacy of direct-acting antiviral agents for the treatment of hcv in rheumatic diseases: case series. (15th June 2017) - Ditto, MC; Talotta, R; Parisi, S; Gerardi, MC; Batticciotto, A; Rigamonti, F; Puttini, P Sarzi; Fusaro, E; Antivalle, M
Abstract : Background: Until approximately 5 years ago interferon (IFN) associated with Ribavirina (RBV) was the gold standard of HCV therapy. Literature data shown that IFN could exacerbate symptoms related to the autoimmune diseases, and flares or intolerance are reported. Recent advances in antiviral therapy had completely modified the HCV infection approach. Direct acting antiviral agents (DAAs) are more efficacious, safer and more tolerable of IFN-HCV treatment. Objectives: To show safety and efficacy of IFN-free HCV eradication in inflammatory arthritis patients with concomitant immunosuppressive treatment. Methods: We evaluated 5 patients (M:F=4:1; median age 50±13.4), affected by inflammatory arthritis and concomitant HCV infection requiring eradication, treated with cDMARDs or bDMARDs (anti-TNFα) and DAAs. Demographic data and concomitant medications are showed in table 1 . Results: Patient 01 and 02 were affected by psoriatic arthritis with severe cutaneous and articular involvement. The first one was also under Lamivudina treatment because concomitant HBV infection and cirrhosis. Patient 03 was affected by enteropathic arthritis (RCU), treated with AZA 100 mg. Patient 04 was affected by rheumatoid arthritis and latent TBC under Nicizina 300 mg daily treatment. Patient 05 was affected by ankylosing spondylitis. Before starting DAAs he was treated with Telaprevir/Peg-IFN/RBV but during the treatment vulgar psoriasis with diffuse and severe involvement appeared. IFN-therapy was interrupted and DAAs therapy started with no flares or other adverse events. Four patients (01, 02, 04, 05) were under anti-TNF-α treatment and 1 patient (03) was under Azatioprina treatment. During therapy with DAAS any flare of autoimmunity disease or adverse events were observed. HCV-RNA was undetectable after 3 months in 4 patients and after 6 months in 1 patient. Conclusions: For all of patients IFN-free therapy was efficacious (blood-HCV-RNA undetectable after treatment) and safe (no adverse events). DAAs therapy could be the best choice to HCV eradication in patients affected by autoimmune rheumatic diseases treated with immunosuppressive drugs. References: Kohtaro Ooka and Joseph K. Lim, Treatment of Hepatitis C in Patients Undergoing Immunosuppressive Drug Therapy, Journal of Clinical and Translational Hepatology 2016 vol. 4 | 206–227. Disclosure of Interest: None declared